Adaptive-lubricating PEO/Ag/MoS2 multilayered coatings for Ti6Al4V alloy at elevated temperature. (5th October 2016) - Qin, Yongkun; Xiong, Dangsheng; Li, Jianliang; Jin, Qitong; He, Yong; Zhang, Rongchu; Zou, Yiran
Abstract: To improve the tribological properties of titanium alloy at elevated temperatures, a multilayered lubricating coating was fabricated on the surface of Ti6Al4V alloy, involving an oxide ceramic coating deposited by PEO treatment, an electroplating Ag coating and a burnished MoS2 film. The tribological properties were evaluated by a ball-on-disk high temperature tribometer over a wide temperature range (RT-600 °C). The results showed that the low friction coefficient and high wear resistance were exhibited at room and medium temperatures (< 350 °C) due to the effective lubrication of MoS2 and Ag layers and the high load supports provided by hard PEO coating. At high temperatures (> 350 °C), the oxidation of MoS2 topcoats and the adhesive wear of softened Ag led to the direct contact of Si3 N4 /exposed oxide underlayer giving rise to the rapid increase of friction coefficient. As the temperature increased to 600 °C, the friction coefficient sharply decreased to a low level 0.2, which was attributed to a combined effect of the diffused Ag from discharged reservoirs, the presence of high temperature lubricants (MoOx, Ag2 MoO4 ) and the formation of lubricants/lubricating glaze layers contact. Graphical abstract: Highlights: A multilayered PEO/Ag/MoS2 lubricating coating is deposited on Ti6Al4V alloy. Ag interlayer benefits to improving wear resistance of PEO coatings at 350–600 °C. PEO/Ag/MoS2 coating exhibits low friction over a wide temperature range (RT-600 °C). Ag2 MoO4 glaze layer formed on Si3 N4 ball provides lubrication at high temperature.